2010
DOI: 10.1590/s1516-35982010001300048
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition, microbiota, and endotoxin-related diseases in dairy cows

Abstract: -In this review article we present an overall summary of the role that high-grain/low forage diets have on rumen composition of microbiota and how changes in the diet affect the release of bacterial cell wall components that are toxic to the host. One of these toxic compounds is lipopolysaccharide or endotoxin, a component of the outer membrane of all Gram-negative bacteria. Moreover, data are provided that support the concept that endotoxin translocates into the blood circulation and show that rumen endotoxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(96 citation statements)
references
References 51 publications
2
91
0
1
Order By: Relevance
“…Ametaj et al (2010) observed that a strong negative relationship between preprandial rumen pH and concentration of LPS in the rumen fluid. Thus, rumen pH modifiers could affect the endotoxin concentration.…”
Section: Discussionmentioning
confidence: 95%
“…Ametaj et al (2010) observed that a strong negative relationship between preprandial rumen pH and concentration of LPS in the rumen fluid. Thus, rumen pH modifiers could affect the endotoxin concentration.…”
Section: Discussionmentioning
confidence: 95%
“…3,4 Early postpartum, cows encounter various immunogenic substances, such as LPS and lipoteichoic acid (LTA), which are important components of the Gram-negative and Gram-positive bacterial cell wall, respectively. 5 Additional exposure of mucosal layers to LPS and LTA occurs owing to accumulation of cell-free LPS or LTA in the rumen when cows are switched from a roughage-rich to a grain-rich diet 6,7 at the onset of lactation. However, the virulence properties of those immunogenic compounds are highly influenced by the sudden switch in diet postpartum.…”
Section: Introductionmentioning
confidence: 99%
“…Recent data have suggested that blood LBP might be used as a biomarker for downer cow syndrome (DCS). An observational study by Ametaj et al (2010) showed a strong association between DCS and plasma LBP (a 10-fold increase) at 7 d before parturition. Moreover, results indicated that cows affected by DCS had lower anti-LPS IgG and greater concentrations of anti-LPS IgM.…”
Section: Fatty Liver and Downer Cow Syndromementioning
confidence: 98%